2019
DOI: 10.1177/0972262919840202
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Environmental Sustainability and Human Development Index: A Case of Selected South Asian Nations

Abstract: All the economists today have established that externalities (free-rider issues) and public goods are the leading causes of market failure, holding the utmost level of relevance of environmental economics. Pollution types can be segregated physically based on the channels (water, air and land) or the sectors responsible for causing it (e.g., industry, electricity generation, transport, agricultural waste disposal, etc.). Thus, sustainability emerges as a key challenge of the twenty-first century for public thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…They (Ghodrati et al, 2018) found that per capita income has an N-shape relationship with EPI, suggesting mixed results depending on the HDI level of the group of countries considered. Jain and Nagpal (2019) indicate a positive influence of HDI on EPI in five South Asian countries during 2002 and 2016 proving that higher HDI leads to smaller damage to the environment and to a better environmental performance.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…They (Ghodrati et al, 2018) found that per capita income has an N-shape relationship with EPI, suggesting mixed results depending on the HDI level of the group of countries considered. Jain and Nagpal (2019) indicate a positive influence of HDI on EPI in five South Asian countries during 2002 and 2016 proving that higher HDI leads to smaller damage to the environment and to a better environmental performance.…”
Section: Literature Reviewmentioning
confidence: 90%
“…In their study, Jain and Nagpal (2019) suggest that urbanization, energy use, and population density negatively impacts EPI in five South Asian nations during 2002 and 2016. Pourali et al (2019) demonstrated a positive influence of GDP per capita on EPI for 101 countries during 2005-2015, same relationship being reported between trade openness, political-civil liberties, good governance, government effectiveness, rule of law, and EPI.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Products/ processes/raw material Use of industrial enzymes and biocatalysis; green manufacture; total quality management; production of special chemicals; Green Technology Glänzel & Zhou (2011), Dögl & Holtbrügge (2014, Kumar et al (2017), Jain & Nagpal (2019), Trivedi & Sharma (2017), Binod et al (2013)…”
Section: Practices In India Sub-practices Authorsmentioning
confidence: 99%
“…The results of empirically proven studies that there is a positive and significant relationship between HDI and EQ are, among others, conveyed by (Shanty et al, 2018) that human quality positively affects environmental quality. The Human development index, positively related to the environmental performance index, explained that the higher accumulation of human resources would lower environmental damage and better environmental performance (Jain and Nagpal, 2019). Education is proving to reduce emissions (Balaguer and Cantavella, 2018).…”
Section: Introductionmentioning
confidence: 99%